2015
DOI: 10.1108/lht-12-2014-0115
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging apps for research and learning: a survey of Canadian academic libraries

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Academic libraries need to leverage the growth in the use of apps. They have a commitment to keep faculty and students educated about resources that can improve their exploration, instruction and learning; smartphones can provide vital apps with features that help academic libraries enhance their services and meet students’ demands (Canuel and Crichton, 2015). Caniano and Catalano (2014) showed that students using smartphones are more likely to use library services – signifying that apps present libraries with an important opportunity to give the general population what they need and want.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Academic libraries need to leverage the growth in the use of apps. They have a commitment to keep faculty and students educated about resources that can improve their exploration, instruction and learning; smartphones can provide vital apps with features that help academic libraries enhance their services and meet students’ demands (Canuel and Crichton, 2015). Caniano and Catalano (2014) showed that students using smartphones are more likely to use library services – signifying that apps present libraries with an important opportunity to give the general population what they need and want.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the library, this experience demonstrated the need to align collection development plans with the shift we see in the communities we serve [14]: a shift to online instruction. Criteria for selecting mobile Journal of the Medical Library Association 108 (2) April 2020 jmla.mlanet.org resources mirror those of physical items in many ways, in other words, content, cost, currency, scope, subject relevance, access, and updates [15].…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for selecting mobile Journal of the Medical Library Association 108 (2) April 2020 jmla.mlanet.org resources mirror those of physical items in many ways, in other words, content, cost, currency, scope, subject relevance, access, and updates [15]. However, additional factors must also be considered due to the digital format of the resource [14][15][16], including consideration of supported platforms; ease of authentication; technical feasibility, implementation, and compatibility with other library hardware and software; functionality and reliability; access options to easily disseminate licenses; promotion of the resource; persistency of content; and updates and vendor support [15][16][17]. In our case, we also had to consider discipline-specific needs, such as the app's ability to replace information acquired during cadaver dissection and the duplication of resources because the library already licensed HAA.…”
Section: Discussionmentioning
confidence: 99%
“…Examples using surveys to obtain similar information were examined (Kumar, 2014, Canuel and Crichton, 2015, Becker et al, 2013, Mills, 2009. This helped with phrasing questions and determining survey length.…”
Section: Data Collectionmentioning
confidence: 99%